Studentų informacijos poreikiai ir jų tenkinimo problemos aukštosiose mokyklose - Stalnionienė, Eglė (Knygotyra, 1988)
The higher school forms reading, social, and professional interests of the students. The investigation of students' information needs enables better service to readers, improves the promotion of books, enhances reference and bibliographic work, and creates optimal methods in information skills training.The article analyzes students' information needs, ways of satisfying these needs, readers' attitudes towards library resources, and the use of information opportunities in universities in Ukraine, Moscow, Vilnius, and other higher education institutions in our country.Based on students' interests, purposes of their activities, and work in scientific and social circles, six types of students were identified. By connecting these types with the students' information culture formation program, it is possible to develop the structure of students' information needs. The article provides suggestions for training information users. On one hand, it helps to meet students' information needs, and on the other, it trains creative information users and creators of new information.